483 Neonatal RSV positive bronchiolitis with fulminant viral septic shock. (17th August 2022) - Gulam Ghouse, Zakir Hussain; Javed, Mehwish; Akram, Muhammad; Rodriguez, Amanda Diaz
Abstract : Aims: Main purpose of presenting this clinical case is that RSV BRONCHIOLITIS can present with lobar pneumonia, Fulminant viral septic shock with DIC, pulmonory haemorrhage and asystole. Viral VS Bacterial sepsis- clinically difficult to differentiate. Methods: 1 month old girl, unwell for 2 days with cough, decrease oral intake, seen by GP in the morning and diagnosed as BRONCHIOLITIS, same day evening presented to the hospital with apnoea in the car arrived at PAU within 3 mins of apnoea.O/E-no HR or breathing, bleeding from nose and mouth, pale looking, mottled, CRT 5 sec.CPR started and connected to monitor showed asystole.Immediate cardiac arrest call was activated.Intubated, cannula inserted, 2 doses of adrenaline given IV, Bolus of normal saline 10mls/kg thrice, partial septic screening done and covered with triple antibiotics amoxycillin, gentamycin and cefotaxime.After 10 mins of resuscitation baby responded. Given vitamin K and transfused with O negative blood and FFP.Blood gas showed mixed metabolic and respiratory acidosis and hence connected to ventilator started on morphine, maintenance fluids, ionotropes, morphine infusion and transferred to tertiary centre. In tertiary centre admitted for 11 days, extubated to CPAP on day 5, weaned to high flow on day 6, RA on day 9. Ionotropes for 1 day, acylovir, vitamin k for 9 and 6 days respectively.Neuroprotective measures followed. Results: NPA for RSV positive, covid 19 PCR negative, blood c/s, CSF c/s and CSF PCR for bacteria and viruses negative, X ray chest consolidation upper lobes bilateral, CT Angiogram subsegmental consolidation and possible intraparenchymal haemorrhage. Initial Echo pulmonory hypertension and repeat Echo normal.MRI Brain -hypersensitivity in posterior putamina. Deranged coagulation profile.APTT more than 180, PT 16.2, INR 1.4 Conclusion: RSV positive bronchiolitis with all complications can mimic bacterial sepsis and its clinically difficult to differentiate between viral and bacterial septic shock.As this baby's blood C/S was negative only positive thing was RSV in NPA, We have to consider this case as RSV BRONCHIOLITIS with fulminant septic shock with pneumonia, DIC, Pulmonory Haemorrhage leading to Asystole.Management of bacterial and viral Septic shock is pretty much the same except in certain cases we may have to use antivirals drugs when indicated.